Perlindungan Hukum Hak Memunggut Hasil Hutan Bagi Suku Anak dalam di Propinsi Jambi - Amir, Latifah; Mushawirya, Rustian; Windarto, Windarto (Wajah Hukum, 2024)
The right to collect forest products (forestry right) is one of the rights to land originating from customary land law which is then recognized as part of land rights that are permanent in the Agrarian Act Number 5 of 1960. The concept of the right to collect forest products is now interpreted as a right what big entrepreneurs can have in managing forests is of economic values, and not as a basis for the rights of indigenous/local peoples who have a living culture by relying on the existence of forest products. This different interpretation ultimately gave birth to policies and legal actions that deprived indigenous/local peoples of their rights to the forest as stated and recognized by the 1945 Constitution as part of protected customary rights. One of the indigenous/local people who use forest products as their source of life is the Suku Anak Dalam (Orang Rimba) community in the Sarolangun Regency area. The many functions of forest land conversion into industrial plantations, as well as the licensing of business use rights over customary forests make the living space and movement of these communities increasingly limited, even in the end giving birth to various land conflicts between indigenous peoples and forest entrepreneurs in the region. Therefore in the future a law is needed that regulates the right to collect forest products as permanent land rights and can provide justice to indigenous people through legal certainty, where the Suku Anak Dalam community is no longer seen as forest looters, or illegal occupation.